PENGARUH PKG SERASAH KAMPUS UNPATTI DAN LIMBAH PERTANIAN TERHADAP FISIKO-KIMIA TANAH DAN HASIL JAGUNG (Zea mays L.) DI ULTISOL /* Artikel Ditarik */ - Maimuna La Habi; Muhammad Riadh Uluputty; Aminudin Umasangaji (Pattimura Proceeding, 2022)
The aim of the study is to determine the effect of campus waste Granular Compost Fertilizer (GCF) and agricultural waste on soil physico-chemical and corn (Zea mays L.) in Ultisol. The research design using a randomized block design with three replications. Treatment consisted of: no fertilizer (KGSK1), with granular compost 8 t ha-1. (KGSK2), inorganic fertilizer (Urea, SP-36, and KCl), recommended dosage (KGSK3), inorganic fertilizer + granular compost 8 t ha-1 ( KGSK4 ), ½ x dose of inorganic fertilizer + ranular compost 8 t ha-1 (KGSK5), 2 doses of inorganic fertilizer + granular compost 8 t ha-1 (KGSK6), ½ x dose of inorganic fertilizer + granular compost 12 t ha-1 (KGSK7) and 2 times the dose of inorganic fertilizer + granular compost 4 t ha-1 (KGSK8). The results showed that GCF and inorganic fertilizers significantly affect the soil physical that is categorized into heavy bulk density (0.80 g cm-3), soil particle density (2.32 g cm-3), soil porosity (7.79%), fast drainage pore (23.55%), slow drainage pore (8.84%), available water pore (11.63%), and unavailable water pore (11.31%). On the other hand, the plant growth and corn production results amounted to 249.19 cm and 7.89 tons ha-1. The combination of GCF and inorganic fertilizers can increase yields by 35%−48% compared to the application of both inorganic fertilizers and GCF. Excessive application of inorganic fertilizers did not show a significant increase in corn yields. Based on these results, the reduction of a half dose of inorganic fertilizer combined with granular compost 12 t ha-1 revealed the highest of dry shelled corn yield (7.89 t ha-1)